Učinkovito uresničevanje Evropske socialne listine – njen osnovni cilj - Končar, Polonca (Delavci in delodajalci, 2021)
The implementation of the European Social Charter is almost as a rule discussed from the view point of the control mechanisms used by the European Committee of Social Rights. The paper underlines the importance of the domestic enforcement of the Charter. In accordance with the principle of subsidiarity, the the primary responsibility to respect social rights, to prevent violations and to remedy them when they occur lies on the states parties. As regards the effectiveness of the implementation and the justiciability of social rights it is maintained that one can not reduce it only to the justiciability of social rights. It can be assured by other modes.
Keywords: effective implementation; European Social Charter; Evropska socialna listina; interpretativne izjave; iztožljivost; justiciability; načelo subsidiarnosti; sistem nadzora; social rights; socialne pravice; Statements of interpretation; the principle of subsidiarity; the supervision system; učinkovito uresničevanje